Probles mikhailovi, a new enigmatic species of Tersilochinae (Hymenoptera: Ichneumonidae) from Madagascar - Khalaim, Andrey I. (Zootaxa, 2021)
A new species of the genus Probles Förster, P. mikhailovi sp. nov., is described from Central Madagascar. The new species possesses unique venation of the fore wing previously unknown in the subfamily Tersilochinae. The genus Probles is recorded from Madagascar for the first time.